Location of impact on composite plates using piezoelectric rosettes technique - Razzini, Adrielly H. [UNESP]; Lopes, Vicente [UNESP]; Rosa, Vinicius [UNESP] (My University, 2017)
In this work, an approach based on the piezoelectric rosette technique has been developed to locate the point of impact on anisotropic composite plates. Each rosette is composed of three macro-fiber composite (MFC) transducers which present a highly directive response to incoming waves. This characteristic is explored to calculate the strain components in the longitudinal and transverse directions of each sensor. In analogy with electrical resistance strain gages rosettes, the principal strain angle can be found, thus the direction of the incoming wave. Two rosettes suffice to determine the impact location by intersecting the wave directions detected by them. This method is easier to implement than triangulation techniques or neural networks algorithms, not only because there is no need to know the wave speed in the material, but also because it doesn't rely on a model to predict the behavior of a structure. The accuracy of this method is experimentally demonstrated on a 1060x1100x2mm carbon/epoxy plate, formed by 13 plain-weave layers with two piezoelectric rosettes bounded to the surface via cyanoacrylate. The impacts were carried out using a small hammer with hardened steel tip, simulating realistic impacts suffered by an in-service structure. The impact point is determined by the proposed method and compared with the actual location of impact.